Linking Soil Microbial Properties with Plant Performance in Acidic Tropical Soil Amended with Biochar - Halmi, Muhammad Farid Azlan; Hasenan, Siti Nahdiyyah; Simarani, Khanom; Abdullah, Rosazlin (MDPI, 2018)
Soil microbial properties are frequently used as indicators of soil fertility. However, the linkage of these properties with crop biomass is poorly documented especially in biochar amended soil with high carbon:nitrogen (C:N). A short-term field trial was conducted to observe the growth response of maize to biochar treatment in a highly weathered Ultisol of humid tropics and to observe the possible linkage of the measured microbial properties with maize biomass. Soil microbial biomass (carbon (C), nitrogen (N), phosphorus (P)), enzyme activity (β-glucosidase, urease, phosphodiesterase) and gene abundance (bacterial 16S rRNA, fungal ITS) were analyzed. For comparison, total soil C, N, and P were also analyzed. The data revealed no significant linkage of soil C, N, and P with maize biomass. A significant association of enzyme activity and gene abundance with maize biomass was not recorded. Strong positive correlation between maize above ground biomass with microbial biomass N was found (r = 0.9186, p < 0.01). Significant negative correlation was recorded between microbial biomass C:N with maize biomass (r = -0.8297, p < 0.05). These statistically significant linkages observed between microbial biomass and maize biomass suggests that microbial biomass can reflect the soil nutrient status, and possibly plant nutrient uptake. Estimation of microbial biomass can be used as a fertility indicator in soil amended with high C:N organic matter in the humid tropics.